Predicting of Student Graduation Using the Naive Bayes Method - Mayang Sari, Rahayu; Tasril, Virdyra; Wahyuni, Sri; Elsa Putri, Shabrina (Cattleya Darmaya Fortuna, 2024)
The national exam is a national standard evaluation system for primary and secondary education. The national exam itself influences students in how they study to face the national exam. Every student faces their own exam differently, there are students who take it seriously and there are those who take it relaxed. Researchers here designed a system for predicting student readiness in facing desktop-based national exams, which uses data mining techniques with the Naïve Bayes method. The naïve Bayes method is applied to find the greatest probability of predetermined variables including TKJ, Mathematics, Indonesian and English scores to find out whether you are ready or not ready to face the national exam. The result of this research is a system that helps school admins find out students' readiness to face national exams. So that it can be taken into consideration by the school to increase students' interest in learning.